Soluções de alho no controle de nematódeos gastrintestinais em bovinos jovens - Parra, Carla Lieda Cezimbra (2011)
Twenty four Holstein calves and heifers naturally infected were used to evaluate the effect of garlic supply on helminth control. The preparation consisted to triturated garlic, 50%, plus water or alcohol 92º, 50%, orally-administrable on the animals. Treatments (T) consisted of a negative control (T1), garlic at 60 (T2) and 120g on alcoholic extract (T3); 60 (T4) and 120g on aqueous extract/100kg of life weight (T5) and the positive control with Albendasole at 10% (T6). The phitotherapic treatments were repeated after 14th day if the infection was superior to 400 eggs per gram of faeces (EPG). The quantitative and qualitative coproculture technique was performed to evaluate the anthelmintic efficacy of the treatments. During all experimental period (54 days) the mean efficacy of EPG were 43 (T2), 50 (T3), 41 (T4), 61 (T5) and 85% (T6). Differences between treated and control groups was observed in EPG and in relative percentage of infective larvae and the larval development. Partial control was found with the garlic solutions on gastrointestinal nematodes. Better results were found with 120g aqueous extract solution.